2010
DOI: 10.3109/08820139.2010.497831
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Composition of IgM Polymers in Patients Suffering from Recurrent Urinary Bacterial Infections after Bacterial Immunization Treatment

Abstract: IgM is the first antibody produced during the immune response to infection or immunization, and it can be secreted as pentamer (containing a small polypeptide, termed as J chain) or hexamer (lacking J chain). In this paper we have analyzed structural characteristics (by electrophoresis and immunoblot) and anti-bacterial specificity (by enzyme-linked immunosorbent assay) of IgM antibodies purified from female patients suffering from recurrent bacterial infections of lower urinary tract and therapeutically immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Pentamers and hexamers isolated from sera of patients suffering with RUBI have been already characterized in our previous experiments, and our results have shown that these Abs were specific only to bacterial strains that were causing the infection, i.e., Proteus sp., Klebsiella sp. and E. coli (24).…”
Section: Binding Of Human Igm Abs To Bacteriamentioning
confidence: 99%
See 4 more Smart Citations
“…Pentamers and hexamers isolated from sera of patients suffering with RUBI have been already characterized in our previous experiments, and our results have shown that these Abs were specific only to bacterial strains that were causing the infection, i.e., Proteus sp., Klebsiella sp. and E. coli (24).…”
Section: Binding Of Human Igm Abs To Bacteriamentioning
confidence: 99%
“…Structural characteristics of IgM polymers purified from patients with RUBI were analyzed previously (24). In summary, IgM Abs purified from sera of Rs were shown to OD optical density, l/J relative ratios of l and J chain band intensities High l/J value indicates the predominance of hexameric IgM, while low l/J value indicates the predominance of pentameric IgM be pentameric, and their structure was preserved even after immunization with heat-inactivated bacteria.…”
Section: Structural Characteristics Of Purified Igm Absmentioning
confidence: 99%
See 3 more Smart Citations